Bhutan Development Update, April 2015 - World Bank Group (World Bank, Washington, DC, 2015)
Growth rebounded in 2014 along with the lift of restrictions over credit and imports, tourism expansion, and the resumption of hydropower investment. Bhutan’s significant dissaving is illustrated by a large current account deficit. Priority will have to be given to private sector development and asset diversification if Bhutan wants to reduce its vulnerability to donor finance and address rising youth unemployment.